STRUKTUR PASAR DAN KINERJA: STUDI KASUS PADA BANK UMUM DI INDONESIA - Nisa, Chaerani; Mukri, Cotoro; Djamil, Achmad (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
The aim of this study is to find the relationship between market structure and performance of banking industry in Indonesia. Structure Conduct Performance Hypothesis and Relative Market Power Hypothesis are few of hypotheses among others that try to conclude relationship between those variables. This research use commercial banks that operate and alredy give their financial report to Financial Service Authority (FSA) in 2018 as a sample. This study shows that Relative Market Power Hypothesis in Indonesian banking. It means that policies that support bank merger or acquisition is not suitable for Indonesia. Since banks gain their profit by offering diversified product. Keywords: market structure, structure conduct performance hypothesis, relative market power hypothesis.